ANALYSIS OF THE DYNAMICS OF PROSTATE CANCER DIAGNOSIS IN THE REGIONAL HOSPITAL DURING THE PERIOD 2018 – 2022 - Leice, Alevtīna; Valpētere, Inese; Bricina, Natālija; Strode, Iveta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
Prostate cancer is a serious medical problem around the world. In many parts of the world, prostate cancer is the leading cause of morbidity and the second leading cause of death immediately after lung cancer. The largest proportion of cases of malignant prostate tumors is in men aged 60-80 years. The Latgale region has the highest proportion of seniors in the population (22.1%). The aim of this research was to evaluate the dynamics of primary diagnostic results over 5 years period in Daugavpils hospital patients. Objects of the study are 546 patients (men) aged from 47 to 88 years who had a PSA marker and prostate biopsy results (histological responses) collected in the period from 1 January 2018 until 1 July 2022. For quantitative evaluation of histological data, the Gleason score was used, as well as its derivative GRADE (degree of malignancy). To assess the dynamics of the quality of diagnostics of prostate cancer over 5 years, the correlation coefficient between the data on the Gleason score of newly diagnosed cancer and the 5 years period of the study was used. Relationships between PSA values, Gleason scores and patient age were also assessed. The SPSS data Statistics program was used for calculation. Difficulties in diagnosis in older patients were discussed.